2010
DOI: 10.1016/j.febslet.2010.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of cytokine signalling (SOCS) 1 and 3 enhance cell adhesion and inhibit migration towards the chemokine eotaxin/CCL11

Abstract: a b s t r a c tSuppressors of cytokine signalling (SOCS) proteins regulate signal transduction, but their role in responses to chemokines remains poorly understood. We report that cells expressing SOCS1 and 3 exhibit enhanced adhesion and reduced migration towards the chemokine CCL11. Focal adhesion kinase (FAK) and the GTPase RhoA, control cell adhesion and migration and we show the presence of SOCS1 or 3 regulates expression and tyrosine phosphorylation of FAK, while also enhancing activation of RhoA. Our no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…When the ratio of activity of these small GTPases is no longer optimal for the protrusion and polarization of the cell, migration will be influenced (40). Constitutively active RhoA may impede cell motility (20,41,42). One of the downstream effectors of RhoA is Rho kinase, which can be effectively inhibited by the compound Y-27632 (28,43).…”
Section: Discussionmentioning
confidence: 99%
“…When the ratio of activity of these small GTPases is no longer optimal for the protrusion and polarization of the cell, migration will be influenced (40). Constitutively active RhoA may impede cell motility (20,41,42). One of the downstream effectors of RhoA is Rho kinase, which can be effectively inhibited by the compound Y-27632 (28,43).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have shown that SOCS3 also inhibits granulocyte macrophage-colony stimulating factor (GM-CSF) and IL-4 signalling to regulate dendritic cell (DC) maturation [10] and that SOCS3 targets focal adhesion kinase (FAK) and Ras homolog gene family, member A (RhoA) to block migration towards the allergic chemokine CCL11 [11]. A key role for SOCS3 in the regulation of IL-6 signalling was identified by conditional knock out (KO) of SOCS3 in murine liver and macrophages, resulting in prolonged activation of STAT1 and STAT3 [8], while an inhibitory role for SOCS3 in IFN signalling has been widely documented to confer resistance to treatment for Hepatitic C virus (HCV) infection [12].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 2, SOCS1 localizes to the microtubule organizing center (MTOC) (44) as does SOCS3 (45). Both SOCS1 and SOCS3 enhance FAK- and RhoA-activation leading to increased cell adhesion and reduced migration (46). …”
Section: Host Cell Cytoskeletal Reorganization Mediated By Ifn-γmentioning
confidence: 99%